Transformation and diversification of Banten TV business as local television industry in the digital era - Amin Aminudin; Ana Nadhya Abrar; Novi Kurnia (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2023)
The digital era has changed all aspects of life, including the aspects of the broadcasting industry. The presence of Internet technology also presents a new system in the broadcasting industry. changes in the broadcasting system have also resulted in business diversification in the broadcasting industry. in this digital era, it has also tightened the business competition in the broadcasting industry, such as Banten TV. The formulation of the problem in this study is how to transform and diversify Banten TV's business in maintaining the broadcasting industry business. The method used in this study is a qualitative method with a case study approach by exploring the transformation and Diversification of the Banten TV Business; the paradigm used is constructivism with the theory of media ecology from Marshall McLuhan. Hasi research shows that Banten TV, as the largest local television in Banten province, transforms broadcast content by broadcasting entertainment and local wisdom, such as the local culture and religion in Banten province. With broadcast coverage using a 5000-watt transmitter, it certainly has a potential role in raising local wisdom with a very wide radiance; the transformation of Banten TV broadcast content is carried out by raising a religious superior program with the name of the Sholawat program (Solusi Tepat Per erat Umat) as a superior program in raising local wisdom in Banten which is religious and also the exploration of tourist destinations in the Banten region. In addition to transforming content, Banten TV also diversified its business by creating television program programs in collaboration with the Banten provincial government as a strategy for increasing the company's economic value